2009
DOI: 10.1121/1.3257206
|View full text |Cite|
|
Sign up to set email alerts
|

What makes a melody: The perceptual singularity of pitch sequences

Abstract: This study investigated the ability of normal-hearing listeners to process random sequences of tones varying in either pitch or loudness. Same/different judgments were collected for pairs of sequences with a variable length (up to eight elements) and built from only two different elements, which were 200-ms harmonic complex tones. The two possible elements of all sequences had a fixed level of discriminability, corresponding to a d(') value of about 2, irrespective of the auditory dimension (pitch or loudness)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
64
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(73 citation statements)
references
References 37 publications
(16 reference statements)
7
64
2
Order By: Relevance
“…1, panel (A), with the smaller filled circles indicating mean performance for the five younger listeners and the smaller open circles the seven older listeners. These values are higher than those reported for tonal stimuli (3.5 dB; Cousineau et al, 2009) or even for roving-level noise bursts (4 dB; Heinz and Formby, 1999). A mixed-measures analysis of variance showed that the differences among bursts were statistically significant ͑F 2,20 = 4.66, p Ͻ 0.05͒ but there was no significant main effect of age group ͑F 1,10 = 2.26, p = 0.164͒ or interaction ͑F 2,20 = 0.32, p = 0.73͒.…”
Section: Resultscontrasting
confidence: 53%
See 2 more Smart Citations
“…1, panel (A), with the smaller filled circles indicating mean performance for the five younger listeners and the smaller open circles the seven older listeners. These values are higher than those reported for tonal stimuli (3.5 dB; Cousineau et al, 2009) or even for roving-level noise bursts (4 dB; Heinz and Formby, 1999). A mixed-measures analysis of variance showed that the differences among bursts were statistically significant ͑F 2,20 = 4.66, p Ͻ 0.05͒ but there was no significant main effect of age group ͑F 1,10 = 2.26, p = 0.164͒ or interaction ͑F 2,20 = 0.32, p = 0.73͒.…”
Section: Resultscontrasting
confidence: 53%
“…Listeners of all ages asked to make judgments about stimuli embedded in rapidly changing sequences tend to do worse for longer sequences and later arriving stimuli (e.g., Vachon and Tremblay, 2005;Cousineau et al, 2009). If aging is associated with specific temporal impairments, then it becomes very important to understand the baseline ability of listeners to make temporal judgments for sequential stimuli.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These issues in part motivated our investigations of whether contour and interval representations-two components of relative pitch-might be the product of specialized mechanisms. Previously, we found that listeners could perceive contours in loudness and brightness nearly as well as in pitch Cousineau et al, 2009͒, suggesting that contour representations are not specialized for pitch. Our present results suggest that the same is true for pitch intervals-when compared to other dimensions, basic pitch discrimination, not pitch interval discrimination, stands out as unusual.…”
Section: Discussionmentioning
confidence: 99%
“…For example, according to Schenker (1935Schenker ( /1979, "all rhythm in music comes from counterpoint and only from counterpoint," and Everett (2000) states that "pitch relationships are of central importance, forming the core of the structure, the identity, and even many of the expressive capabilities of pop-rock music." Empirical work demonstrates that pitch is the fundamental organizing principal for musical memory (Dowling, 1978;Hébert & Peretz, 1997), recognition (Dowling & Fujitani, 1971;White, 1960), similarity judgments (Cousineau, Demany, & Pressnitzer, 2009;Eerola, Järvinen, Louhivuori, & Toiviainen, 2001), segmentation (Dawe, Platt, & Racine, 1993, 1994, perceived stability (Bigand, 1997), and the overall formation of a mental representation of music (Krumhansl, 2000).…”
Section: Introductionmentioning
confidence: 99%